Answer:
j = -6
Step-by-step explanation:
j + 2j + 3j = -20 + (-16)
6j = -36
j = -6
Answer:
1. Linear
2. Not Linear
3. Linear
4. Linear
Step-by-step explanation:
<u>Function 1</u>
Linear, follow a sequence of 4, 3
<u>Function 2</u>
Not Linear, does not follow a sequence
<u>Function 3</u>
Linear, follow a sequence of 1, 0
<u>Function 4</u>
Linear, follow a sequence of 3, -1
I think it's -35. The steps to get that number is subtracting the 3 to the right side. Then you have -2 - 3 which equals to -5. Then you still have x/7= -5. Get rid of 7 from the x and do the same thing to the other side but you multiply 7 and -5. Last you your would be x= -35.